When police become postgraduates : an intertextual analysis of research proposals in the MTech Policing degree at an ODL university - Ndlangamandla, Sibusiso Clifford (2015)
This research poses the question: How do professional and academic discourse practices amongst MTech Policing postgraduate students intersect in the research proposal at an Open Distance Learning (ODL) institution? The research proposal is chosen as the site for investigation because it is a contested, 'gatekeeping mechanism' which can be challenging for many students, and for their supervisors. This is a particular challenge in the current rapidly changing postgraduate sector, in which there is increased mobility between workplace domains and the university, as students return to study on a part-time basis. The study is located in the field of academic literacies, which challenges deficit framing of student writing through the analysis of both texts and their social practices. It uses critical discourse analysis (CDA), with ethnographic framing, in order to explore and describe how professional practices in policing in post-apartheid South Africa are recontextualised in academic writing. A cross section of proposals was analysed using analytical tools such as intertextuality and interdiscursivity. In the university setting, interviews were conducted with supervisors and workshops on research methods were observed. In order to understand workplace-based practices, students were interviewed at their sites of work across the country. A hybrid curriculum model was introduced to understand the intersection of the professional, workplace, and university domains suggested by Lee et al. (2000). The findings suggest that the way students draw on the workplace, both intertextually and interdiscursively in their academic texts, results in tensions and discourse clashes between the workplace and academic knowledge practices. Whereas the academy values reflection, critical consciousness, and theoretical knowledge, the policing context puts a primary value on practice-based knowledge, compliance with rules, and the police sub-culture. Through dialogue with the researcher, students' interpretations of their texts revealed their workplace and professional identities, notions of genre and discourse, and at times unequal power relations between different institutions. The tensions were most evident in the different audiences for which students were writing, and in the way students identified key concepts for their proposal, and how they negotiated ethics permission. The policing context was more prominent than the academic setting. However, students also show agency and strong awareness of audience through their recontextualisation strategies and hybridity in the writing of the proposal genre. This had an impact on transitions between discourse communities and on the intersection of discourses in postgraduate academic literacies. This research shows the contribution of CDA and ethnographic framing, in combination with a hybrid curriculum model, in uncovering the nature of the tensions that students experience in writing their research proposals. This has potential for informing supervisors and writing instructors in the ODL context by providing a better understanding of the challenges that students face. The study concludes with strategies for teaching academic literacies to MTech policing students